An Investigation of the Impacts of the Blasts in A Mining Process Upon A Concrete Shaft Lining - Rozycki J (The Australasian Institute of Mining and Metallurgy, 1987)
The results of shaft lining monitoring gave rise to an investigation of cracks observed in the structure. An hypothesis was made that the cracks might be due to stresses caused by energy wave propagation, triggered during blasting or by the rock falls. However, it could not be excluded that the cracks had their origin in the rheologic changes taking place in the concrete. To prove the hypothesis, an investigation of the scale of the increase of stress due to the energy triggered was undertaken. At the same time it was decided to attempt to determine the "damage threshold" for such material in the danger zone. In the paper the investigation and its results are presented, as conducted in one of the shafts. In conclusion, certain generaliza- tions are proposed to give a starting point in the consideration of similar problems elsewhere.